Women's Empowerment and Economic Development: A Feminist Critique of Storytelling Practices in "Randomista" Economics. Issue 2 (2nd April 2020) - Kabeer, Naila
ABSTRACT: The 2019 Nobel Prize in economics was awarded to three scholars on the grounds that their pioneering use of randomized control trials (RCTs) was innovative methodologically and contributed to development policy and the emergence of a new development economics. Using a critical feminist lens, this article challenges that conclusion by interrogating the storytelling practices deployed by "randomista" economists through a critical reading of a widely cited essay by Esther Duflo, one of the 2019 Nobel recipients, on the relationship between women's empowerment and economic development. The paper argues that the limitations of randomista economics have given rise to a particular way of thinking characterized by piecemeal analysis, ad hoc resort to theory, indifference to history and context, and methodological fundamentalism. It concludes that the randomista argument that broad-based economic development alone – without focused attention to women's rights – will lead to gender equality has not been borne out by recent data. HIGHLIGHTS Despite claims of impartiality, Duflo's interpretations of evidence and the language she uses indicate that the randomista method and narrative is not objective or impartial. The randomistas' treatment of preferences as random and idiosyncratic ignores what feminists have long espoused: that the formation of preferences derives from entrenched social constructions. The randomistas' claims to methodological superiority result in a discounting or dismissal of findings from nonexperimental studies in favor of experimental studies that report the same findings. Duflo's main argument discussed in this paper is that while gender equality is desirable in its own right, it is better achieved through gender-neutral policies because gender-affirmative policies "distort" the allocative process and lead to efficiency costs. Yet, these so-called distortions stem from historical structures that have curtailed women's productive potential and protected male privilege. In other words, patriarchal discrimination introduces structural costs that are unlikely to be visible when the focus is on individual economic actors.